2010
DOI: 10.1177/0961203310367918
|View full text |Cite
|
Sign up to set email alerts
|

TNIP1, SLC15A4, ETS1, RasGRP3 and IKZF1 are associated with clinical features of systemic lupus erythematosus in a Chinese Han population

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease with heterogeneous clinical manifestations influenced by genetic and environmental factors. Five novel susceptibility genes (TNIP1, SLC15A4, ETS1, RasGRP3 and IKZF1) for SLE have been identified in a recent genome-wide association study of a Chinese Han population. This study investigated their relationships with disease subphenotypes, including renal nephritis, photosensitivity, antinuclear antibody (ANA), age at diagnosis, malar rash, discoid rash, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
73
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(82 citation statements)
references
References 28 publications
8
73
1
Order By: Relevance
“…This would suggest that, in SLE patients, the expression of Ikaros would be decreased compared with normal controls. Indeed, a report by Hu et al (24) does imply that in peripheral blood mononuclear cells from SLE patients, Ikaros mRNA levels are reduced (23). Whether this difference in expression of Ikaros translates to the regulation of PP2A remains to be seen.…”
Section: Discussionmentioning
confidence: 99%
“…This would suggest that, in SLE patients, the expression of Ikaros would be decreased compared with normal controls. Indeed, a report by Hu et al (24) does imply that in peripheral blood mononuclear cells from SLE patients, Ikaros mRNA levels are reduced (23). Whether this difference in expression of Ikaros translates to the regulation of PP2A remains to be seen.…”
Section: Discussionmentioning
confidence: 99%
“…The ABIN(D485N)-expressing mice develop all the hallmarks of autoimmunity and succumb to a disease that resembles Type III and Type IV lupus in humans, termed lupus nephritis (Nanda et al, 2011;Caster et al, 2013). Interestingly, polymorphisms in the human gene encoding ABIN1 predispose individuals to several autoimmune diseases (Han et al, 2009;Nair et al, 2009;He et al, 2010;Gregersen et al, 2012;Yang et al, 2013). Autoimmunity in ABIN1(D485N) knock-in mice is suppressed when they are crossed to MyD88-deficient mice, demonstrating that the aberrant activation of the signalling network underlies the phenotype (Nanda et al, 2011).…”
Section: How the Signalling Network Is Activated Formation Of The Mydmentioning
confidence: 99%
“…45 The associations of those TNIP1 variants were also replicated in Japanese (rs7708392) and Chinese Han (rs10036748) populations. 46,47 There was a stronger association for rs7708392 with LN in the Japanese population. 46 A replicate study of rs7708392 and rs10036748 in a southwest Chinese SLE population found a weak association, but as for the Japanese population, a significant association for rs7708392 with LN in their SLE population was apparent.…”
mentioning
confidence: 99%